Synthesis, Characterization and Antibacterial Activity of Copper(II) Complexes with N-Vanillidene-2-amino-4-phenylthiazole - ASHALEKSHMI, V.S.; MOHANAN, K. (Asian Journal of Chemistry, 2010)
Condensation of 2-amino-4-phenylthiazole with vanillin yielded a potentially bidentate Schiff base (VAAT) which formed a series of Cu(II) complexes of the type [Cu(VAAT)X2] in presence of different counter anions such as chloride, bromide, nitrate, acetate and perchlorate. These complexes were characterized by elemental analysis, molar conductance, magnetic susceptibility measurements and IR spectral studies. Spectral studies revealed that the ligand is bonded to the metal ion through azomethine nitrogen and ring nitrogen atoms. The ligand as well as the complexes were screened for their antibacterial activity against selected bacterial stains such as P. aeruginosa, K. pneumoniae, B. megaterium, V. cholerae, S. typhi. It has been observed that the complexes are more potent bactericides than the ligand and the activity varied with the change in the coordinating anion.